POLA KARIER, KOMUNIKASI ORGANISASI, MOTIVASI BERPRESTASI, KOMITMEN ORGANISASI DAN KINERJA KARYAWAN - Sang Ayu Kompiang Mahartini (Universitas Pendidikan Nasional, 2013)
Performance is a common word used to perceive the level of achievement employee incarrying out the duties and responsibilities given. But how to work on improving theperformance, to a wide range of studies and research that question is answered. To answerthat conducted the study by examining the variabels that affect employee performance. As forthe variables studied were Career Patterns, Organizational Communication, AchievementMotivation, Organizational Commitment and Employee Performance.The research was conducted at District of Kuta Badung Regency with the number ofrespondents 126 peoples. Analysis technique used is Structural Equation Modelling (SEM)using Amos Software for Windows version 16.00.The results of analysis showed that the Career Patterns had a positive and significantinfluenced to Achievement Motivation with standarized estimate (regression weight) of 0.356,the Organizational Communication had a positive and significant influenced toOrganizational Commitment with standarized estimate (regression weight) of 0.422, theCareer Patterns had a positive and significant influenced to Organizational Commitmentwith standarized estimate (regression weight) of 0.256, the Organizational Communicationhad a positive and significant influenced to Achievement Motivation with standarizedestimate (regression weight) of 0.401, the Career Patterns had a positive and significantinfluenced to Employee Performance with standarized estimate (regression weight) of 0.383,the Organizational Commitment had a positive and significant influenced to EmployeePerformance with standarized estimate (regression weight) of 0.409 and the OrganizationalCommunication had a positive and significant influenced to Employee Performance withstandarized estimate (regression weight) of 0.246. While the Career Patterns had a positiveand insignificant influenced to Employee Performance with standarized estimate (regressionweight) of 0.166. Determination Analysis showed that the Career Patterns, OrganizationalCommunication, Achievement Motivation and Organizational Commitment had of 74,7%influenced on changes in Employee Performance.Keywords : Career Patterns, Organizational Communication, Achievement Motivation,Organizational Commitment and Employee Performance.